2022
DOI: 10.3390/ijerph192013177
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Conceptional Anti-Thyroid Antibodies and Thyroid Function in Association with Natural Conception Rates

Abstract: Thyroid functioning is an integral part of the endocrine system that supports conception and pregnancy. Frequent consumption of seafood and iodine by Japanese people may adversely affect their thyroid function. Thus, in this study, we aimed to analyze the associations between iodine intake, thyroid hormones, autoimmunity, and natural conception rates in Japanese women trying to conceive their first child. A prospective study of 24 weeks targeted 80 women with no history of infertility, who did not plan to unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Similarly, TPOAbs, but not TSH, were correlated with lower live birth rates and higher miscarriage rates in a study of 1468 infertile women [ 157 ]. In the same way, a more recent study of women without infertility found a negative association between TPOAbs levels and natural conception rates [ 158 ]. Investigating the impact of TSH levels versus those of autoimmunity, d’Assunção et al identified no differences in pregnancy rates among infertile women with AITD undergoing IVF when comparing ‘low’ vs. ‘high’ TSH (<2.5 vs. >2.5 mU/L) [ 159 ], suggesting that autoimmune destruction rather than reduced serum TSH links thyroid and reproductive pathologies.…”
Section: Thyroid Hormones and Reproductive Physiologymentioning
confidence: 82%
“…Similarly, TPOAbs, but not TSH, were correlated with lower live birth rates and higher miscarriage rates in a study of 1468 infertile women [ 157 ]. In the same way, a more recent study of women without infertility found a negative association between TPOAbs levels and natural conception rates [ 158 ]. Investigating the impact of TSH levels versus those of autoimmunity, d’Assunção et al identified no differences in pregnancy rates among infertile women with AITD undergoing IVF when comparing ‘low’ vs. ‘high’ TSH (<2.5 vs. >2.5 mU/L) [ 159 ], suggesting that autoimmune destruction rather than reduced serum TSH links thyroid and reproductive pathologies.…”
Section: Thyroid Hormones and Reproductive Physiologymentioning
confidence: 82%
“…Higher autoantibody levels in these patients might as well be the culprit behind insufficient response to infertility treatment. 13 , 14 Mounting evidence suggests that inflammation and autoimmunity can cause PCOS. 12 Likewise, a higher prevalence of autoimmunity with PCOS might cause an increased risk of metabolic syndrome, infertility issues and adverse pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%